Traditional Actions: SIREP Influence Cortisol, IFN- and IL-10 In Elderly with Sleep Disorders - Joni Haryanto; Suhartono Taat Putra (Universitas Airlangga, 2016)
Introduction: Sirep, is one of the traditional intervention of people in East Java Indonesia, especially Tengger tribe using spells to meet the needs of human sleep. Elderly in Indonesia is someone who has more than 60 years of age. Elderly in general often experience sleep disturbances fulfillment, But the effects of nursing Sirep as an immunomodulator to the levels of cortisol, IFN-Rα and IL-10 is still unknown in nursing perspective. Method: The population of this study were 70 elderly with the number of respondents were 43 elderly. They were divided into two groups for 23 elderly with 6-month sirep intervention (mean age, 69.6 ± 5.2 years) as an experiment group and 20 elderly as control group (65.8 ± 5.4 years). The need of sleep is implemented to Evaluate the sample of immune modulation, cortisol levels, IFN-Rα and IL10. The molecular biology of the samples was determined using ELISA analysis. The statistical analysis of the data used Determine ANOVA and t-test. Results: After the 6 -month intervention, there re is significant changes in serum cortisol levels (p = 0.0001) and a different test with a control intervention was also significant (p = 0.00 1 3). Significant changes in serumlevels of IFN-Rα is (p = 0.0003) and a different test with a control intervention is also significant (p = 0.016 4), while the change in the levels of IL-10 in serum is significant (p = 0.0003) and test different intervention with no significant control (p = 0.1143). Discussion: This study supports the hypothesis that sirep can improve immune modulator in elderly. However, immune modulator showed a slight improvement in the nursing intervention of sirep group, suggesting that a longer or more frequent sessions of intervention might have an effect.